2016
DOI: 10.1016/j.drugalcdep.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse, risky sexual behaviors, and HIV or syphilis infections among Chinese men who have sex with men

Abstract: Background Few studies have employed standardized alcohol misuse measures to assess relationships with sexual risk and HIV/syphilis infections among Chinese men who have sex with men (MSM). Methods We conducted a cross-sectional study among MSM in Beijing during 2013–2014. An interviewer-administered survey was conducted to collect data on sociodemographics, high-risk behaviors, and alcohol use/misuse patterns (hazardous/binge drinking and risk of alcohol dependence) in the past 3 months using Alcohol Use Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
2
25
1
Order By: Relevance
“…In a recent study in Kenya, among 1476 MSM, 44% of the sample had a hazardous alcohol consumption, and no relationship was found between alcohol and tobacco consumption and HIV infection 29. In another study among 3588 MSM in China, alcohol prevalence was 56.1% with 16.8% of them being binge drinkers and 14.4% being recent hazardous drinkers, using the WHO AUDIT-C scale 30. Recent alcohol misuse was associated with increased sexual and HIV/syphilis risks as well as sexual risk behaviours including alcohol use before sex, sex without condoms and multiple concurrent partnerships.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study in Kenya, among 1476 MSM, 44% of the sample had a hazardous alcohol consumption, and no relationship was found between alcohol and tobacco consumption and HIV infection 29. In another study among 3588 MSM in China, alcohol prevalence was 56.1% with 16.8% of them being binge drinkers and 14.4% being recent hazardous drinkers, using the WHO AUDIT-C scale 30. Recent alcohol misuse was associated with increased sexual and HIV/syphilis risks as well as sexual risk behaviours including alcohol use before sex, sex without condoms and multiple concurrent partnerships.…”
Section: Discussionmentioning
confidence: 95%
“…A prospective cohort study among 1,027 FSW in Uganda found that 78% of the sample reported using alcohol with 71% admitting to using alcohol at least once a week, with a reduced prevalence of 54% after 2 years of intervention 31. This emphasises the need for alcohol risk reduction programme and programme specifically focused on the adoption of safer drinking practices integrated into HIV prevention packages and geared towards highly exposed groups 30 31…”
Section: Discussionmentioning
confidence: 99%
“…After review of potential articles for inclusion, we did not focus on alcohol use/misuse since few recent studies focused solely on alcohol use [2427], and none informed the primary purposes for this review.…”
Section: Methodsmentioning
confidence: 99%
“…The research showed that there is an equal number of young people of both sexes who do not use condoms as a protection against STIs. The most common reason they give for not using condoms during a sexual intercourse is that they have a permanent sexual partner who they believe is faithful and has no STI, because they look healthy and have no changes on the sexual organs [28]. Some of the girls whose partners do not use a condom during sexual intercourse think that they do not need it because they use oral contraceptives [28].…”
Section: Discusionmentioning
confidence: 99%